Study and travel: students’ perceptions on the importance of tourism in mobility - Filipe, Sandra (2020)
This research aims to explore the importance of tourism activities for student mobility, considering the decision process, the experience of the students while on mobility, and their loyalty to the host region, including their cooperation in promoting local attractions among relatives and friends. We present qualitative results obtained from focus groups with Erasmus students from diverse countries inside and outside Europe, who spent at least one semester in the University of Aveiro, Portugal. The discussions explored students’ perceptions, experiences and practices before and during the mobility. Our results include evidence on how traveling opportunities are an inherent part of Erasmus students’ mobility. Overall, their tourist activities are shown as strong enhancers of the learning process while on mobility, despite competing with limited resources of time and money. Traveling is also an opportunity to spend time with family and friends, namely with other mobility students at the same host university, fostering integration and a higher degree of satisfaction with the mobility experience. In turn, the extended exposure to a different language and culture transform mobility students into ideal ambassadors of the host country, contributing significantly to the promotion of their mobility destinations.